Lear and Quijote, two wanderers on uneven paths - Maria de Jesus Crespo Relvas (The Grove, 2019)
King Lear of Britain and Don Quijote de la Mancha, both old and frail, are dwellers of two very different worlds and eras. The ways they were devised and shaped by William Shakespeare and Miguel de Cervantes generate nonetheless diverse similarities that emphatically expose crucial traits of the human nature.